Ion Escape From Mars Through Time: An Extrapolation of Atmospheric Loss Based on 10 Years of Mars Express Measurements. Issue 11 (22nd November 2018) - Ramstad, Robin; Barabash, Stas; Futaana, Yoshifumi; Nilsson, Hans; Holmström, Mats
Abstract: Solar wind‐driven atmospheric ion escape has long been hypothesized as a major influence on the evolution of the Martian atmosphere due to the lack of a Martian global dipole magnetic field. We use 10 years (2007–2017) of Mars Express data to quantify the ion escape rate over the fully sampled parameter space of upstream solar wind dynamic pressure, p dyn, and solar photoionizing flux, F XUV . The modeled dependence on the upstream parameters indicates a near‐linear dependence on F XUV and weak negative correlation with p dyn . Integrating total heavy ion escape back through time, considering the evolution of the upstream parameters and the modeled trends, can only account for an estimated 4.8 ± 1.1 mbar of atmosphere lost as ions since the middle to late Hesperian (∼3.3 Ga ago). Accounting for the recently reported stability of ion escape through the energetic oxygen ion plume provides an upper estimate of ∼6 mbar lost. Extending the extrapolation to the late Noachian (3.9 Ga ago) accounts for 6.3 ± 1.9 mbar, and analogously up to ∼9 mbar, lost through ion escape since that time. Thus, the ion escape trends observed by Mars Express indicate that atmospheric ion escape contributed only a minor role in the evolution of the Martian atmosphere. We also report solar wind control of the cold ion outflow channel, providing a tentative explanation for the low response of the ion escape rate to upstream solar wind. Plain Language Summary: There is plentiful evidence that liquid water was standing, flowing, and precipitating on the surface of Mars early in the planet's geological history. About 3.3 billion years ago the climate that allowed such a wet environment on Mars changed and turned the planet into its present‐day cold and dry state. It is commonly thought that a strong greenhouse effect, sustained by an initially thick atmosphere, collapsed as the atmosphere gradually escaped to space, a process that can be driven by interaction with the solar wind, among other mechanisms. We estimate how much atmosphere has been removed by the solar wind by studying measurements of escaping atmospheric ions as the planet is subjected to varying solar conditions. We find that the solar wind is not a strong driver for the rate of atmospheric ion escape, which is rather driven by solar ionizing radiation. Adding up the estimated ion escape rate over 4 billion years, accounting for the stronger solar wind and solar radiation from the younger Sun, we find that at most roughly 9 mbar surface pressure has been removed by the solar wind through ion escape. This amount is alone too small to explain the removal of the early Martian atmosphere. Key Points: The ion escape rate is weakly inverse dependent on solar wind dynamic pressure and near‐linearly dependent on solar photoionizing flux Atmospheric mass loss through ion escape accounts for ≲ 10 mbar lost since collapse of the Martian hydrosphere The solar wind control of the cold ion escape characteristic energy remains well above escape energy for all expected conditions